Police location pages and groups on Facebook: Does knowing where the police are influence perceptions of certainty and drug driving behaviour?. (March 2022) - Mills, Laura; Truelove, Verity; Freeman, James; Davey, Jeremy
Highlights: Drug driving events were reported by just over half (58.5%) of the sample. A quarter of participants (219) used Facebook for police location (PL) information. Almost two thirds of the 219 PL users were drug drivers (142). A subgroup of PL users (43%) used the information to avoid roadside drug testing. PL users and non-users did not differ in perceptions of certainty or drug driving. Abstract: Motorists can drive past a police roadside operation and share this location to a Facebook police location group or page within seconds. Several of these police location communities (PLCs) exist on Facebook, however the effect of these communities on perceptions of apprehension certainty and offending behaviour(s) remains unknown. This research aimed to explore this further, with a sample of N = 890 Queensland motorists (N = 350 females, N = 532 males) who acknowledged consuming either marijuana, methamphetamine or methyl​enedioxy​methamphetamine in the previous 12 months. One quarter of the sample (N = 219) reported using PLCs, with 94 of these users (43%) reporting using PLCs to avoid Roadside Drug Testing (RDT) (PLC-avoid-RDT). Compared to the police location community (PLC) users who did not use the information to avoid RDT (N = 125), PLC-avoid-RDT users reported a greater level of past offending (75 vs 31 events in past 12 months), demonstrated a greater degree of disordered drug use (M = 16.93 vs 11.82 out of 44), had greater future intentions to offend ("unlikely" to "likely" vs "unlikely" to "very unlikely"), viewed the posts more frequently (few times a week vs a few times a month), and perceived posts to be more accurate and reliable (6.57 vs 5.20 out of 10). This study provides preliminary evidence into the use (and effect) of PLCs among drug takers, and suggests that while these sites are not used by all offenders, a smaller proportion of motorists are using them with the intention of actively avoiding RDT.